Cortical Blindness due to Bilateral Occipital Infarcts in a Renal Failure Patient with Prostate Cancer: A Rare Complication of Hemodialysis - O. G. Doluoglu; M. S. Saricaoglu; C. V. Oztekin; A. Karakurt; A. O. Akdemir; E. Koc (Case Reports in Medicine)
Loss of vision is a rare complication seen in hemodialysis patients. It is thought to develop because of the hypotension that can be observed during dialysis. This paper involves a patient with acute loss of vision during hemodialysis due to bilateral occipital infarcts.